FRAMING CONDITIONALITY OF FOREIGN AID: A CRITICAL APPROACH TO INTERNATIONAL COOPERATION PROCESSES - Vega, María Eugenia; Parra, Oscar (AUSTRAL: Brazilian Journal of Strategy & International Relations, 2023)
The relevance of foreign aid within International Relations is found intrinsically related to the concept of development. However, this one has transformed over the last decades but what remains intact is its conditionality. It is convenient to put foreign aid under an uncanny descriptive scope and content analysis as the development discourses are still changing, but the real underlying motivations of the states continue to be the same. From a realist constructivist approach, this text aims to study critically the forms that foreign aid has taken, especially through two main modalities: North-South Cooperation and South-South Cooperation, though this time framing is employed to study the construction of interests in foreign aid. The text is structured in the following way: framing is located as a constructivist theory in psychology and sociology that gives a logical order to the interpretation of political realities; then, the history of both foreign aid modalities allow to examine the conditions of conditionality; finally, a conclusion is drawn from the framing assessment in relation to the power relations and the construction of global development discourses. This article proposes that both North-South Cooperation and South-South Cooperation still displays the self-interested drive of the modern state.